Developments in Ureteral Stent Technology - Lee, Justin; Katz, Matthew; Shah, Ojas (Frontiers in Surgery, 2021)
Ureteral stents have been utilized for decades in maintaining ureteral patency, most commonly after ureteroscopy in the treatment of urolithiasis. Since their initial development, ureteral stents have had many technological advances that have allowed for better patient outcomes with improvements in comfort, durability, patency, encrustation resistance, biocompatibility, ease of insertion, migration, and biofilm development. Several new ureteral stents enter the market every year, each with their own touted benefits. It is essential to understand the different advantages for each ureteral stent to provide the best available care to patients when possible. The purpose of this review is to give a brief history of ureteral stent development and summarize the recent developments in ureteral stent designs. We aim to review the data supporting the clinical advantages of the latest ureteral stents available for use by urologists.